Sex-Specific Responses to Tacrolimus and Mycophenolate Mofetil in Spontaneously Hypertensive Rats - Marañón, Rodrigo Oscar (2023)
In recent decades, the roles of tacrolimus and mycophenolate mofetil (MMF) in hypertension have been under discussion. However, the question of whether there are sex-specific responses to these agents has not received enough attention. Aim: To evaluate sex-specific differences in the responses to tacrolimus and mycophenolate mofetil in female (F) and male (M) spontaneously hypertensive rats (SHRs) and evaluate whether T cells contribute to mean arterial pressure (MAP) changes. Methods: Male and female SHRs received either tacrolimus or MMF for 14 days. The rats were implanted with radiotelemeters. MAP was measured chronically; then, circulating and renal infiltrated CD4+, CD8+, T helper 17 (Th17), and T regulatory (Treg) cells were quantified using flow cytometry. Key Findings: Tacrolimus increased MAP only in males, and it decreased CD4+ and CD8+ T cells in both males and females (p < 0.05). The tacrolimus-induced reduction of renal CD4+ and Treg cells was more profound in males. MMF reduced MAP and circulating and renal CD4+ and CD8+ T cells in the male and female rats. MMF also decreased Th17 and Treg cells in both sexes, but the decrease in Th17 was higher in males (p < 0.05) and the reduction in Treg cells was higher in females (p < 0.05). Our findings indicate that the effects of tacrolimus and MMF on renal T cell subsets are sex-specific. Significance: Targeting T cells in hypertension using therapeutic agents may have different effects on men and women; so, the management of hypertension and post-transplant hypertension using these agents should be specified by gender.